Training and mentoring for Posyandu cadres as a preventive effort to address stunting through application of cross-sector partnership synergy - Mariyudi Mariyudi; Faisal Matriadi; Ikramuddin; A Hadi Arifin; M Sayuti; Harvina Sawitri; Saifuddin Yunus; Muhammad Subhan; Ibnu Sina; Muhammad Pavel Askari (Buletin Pengabdian Bulletin of Community Services, 2026)
Background and Aim: Stunting is a growth disorder in children under five years old that can hinder physical and mental development. In Lhokseumawe City, 797 children were still enrolled in the stunting reduction program in 2024. This study aimed to improve the knowledge and capacity of Posyandu cadres through training and mentoring activities by implementing cross-sector partnership synergy as a preventive effort to address stunting. Methods: This community service activity was conducted in Blang Pulo Village, Muara Satu District, Lhokseumawe City, and completed on November 11, 2025. The study used a Collaborative Decision Making: Community-Based Methods approach with the SARAR method involving 30 Posyandu cadres. Data were collected through pre- and post-training tests and mentoring evaluations. Results: The training effectively increased participants’ knowledge, as shown by significant improvements in pre- and post-test scores with a significance level of 0.0001 (<0.05). Mentoring activities further strengthened the implementation of knowledge gained during the training. Conclusion: Training and mentoring activities for Posyandu cadres were effective in improving knowledge and strengthening the quality of basic health services at the village level. These activities also served as a community empowerment strategy in preventive efforts to reduce stunting through cross-sector partnership synergy.